POTENTIAL AND CHALLENGES: TOURISM STAKEHOLDERS’ PERCEPTIONS TOWARDS MUSLIM FRIENDLY GEOTOURISM IN LANGKAWI UGGP - Siti Syahirah Saffinee; Mohammad Aizat Jamaludin; Sharina Abdul Halim (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
This study provides the current practices, utilising qualitative data among tourism stakeholders on Muslim Friendly Geotourism (MFGT) in Langkawi UGGp. MFGT has grown as a valuable tourism sector in both Muslim and non-Muslim countries. Langkawi UGGp has a Malay culture, and the majority of the local communities are Muslim. Previous study shows the tourism business has long been part of the so-called ‘unfriendly to Muslim’ faith-based needs. However, the issues were limited of ap-proach related to MFGT concept among tourism stakeholders. Consequently, MFT solves this predicament, allowing more Mus-lims to participate in geotourism activities without having any issues performing their faith. Besides, findings shows the potential and challenges of MFGT to be implemented in Langkawi UGGp. All tourism stakeholders are positive in their responses and aware on the importance of implementation MFGT for Langkawi UGGp economic development, protection of the environment and participation of local community. Therefore, this study strives to enhancing knowledge in geotourism literature, particularly in the cross-cultural context manner.